The Neuroprotective Effect of Irisin in Ischemic Stroke - Liu, Yaqiang; Zhu, Chunhua; Guo, Jiahui; Chen, Yonghong; Meng, Chaoyue (Frontiers in Aging Neuroscience, 2020)
Irisin is a PGC-1α-dependent myokine that causes increased energy expenditure by driving the development of white adipose tissue into brown-fat-like tissue. Exercise can improve irisin levels and lead to its release into the blood. In ischemic stroke, nerve cells are sensitive to energy supply, which leads to the generation of reactive oxygen species that are detrimental to cell survival via mitochondrial dysfunction. As a protein associated with exercise, irisin can alleviate brain injury in the pathogenesis of ischemic stroke. It is thought that irisin can upregulate the levels of brain-derived neurotrophic factor (BDNF), which protects nerve cells from injury during ischemic stroke. Furthermore, the release of irisin into the blood via exercise influences mitochondrial dynamics crucial to maintaining the normal function of nerve cells. Consequently, we intend to summarize the known effects of irisin during ischemic stroke.